A Case of Bilateral Implantation of Diffraction IOL with Extended Depth of Focus in a Patient with a History of Keratorefractive Excimer Laser Surgery - A. A. Kasyanov (Oftalʹmologiâ)
A clinical case of bilateral implantation of EDOF IOL in a patient after LASIK is presented. The standards for assessing visual acuity at an intermediate distance are indicated. A modified version of the test table for the intermediate distance is presented. The obtained functional result corresponds to theoretical ideas about the potential of IOL with a prolonged focus. When calculating the IOL after LASIK, a sufficient degree of accuracy was provided by the formulas Haigis-L, Barrett True-K. The use of data on the total refractive power of the cornea is promising.